Deux textes cunéiformes d’une petite collection privée belge - Lecompte, Camille (Altorientalische Forschungen, 2017)
Two cuneiform texts belonging to a private Belgian collection, respectively an administrative document from the Ur III period and a cone of Gudea bearing a well-known inscription, are published here. The administrative tablet, of unknown provenance, features an interesting onomasticon which is reminiscent of the archives from Puzriš-Dagan, Iri-saĝrig and Nippur.